القيم الاجتماعية في صفوة من الأشعار العربية ببلاد يوربا- نيجيريا: Social Values in selected arabic poems in Yorubaland Nigeria - Ambali, Abdessalami Babatandi (SIBAWAYH Arabic Language and Education, 2020)
Arabic poetry composed by Yoruba Arabic poets is more of Islamic culture in its orientation. The poetic themes explored by the poets include panegyrics, description, admonition and elegy. Greeted with modern trends however, the literary productivity of the Yoruba Arabic poets started experiencing multidimensional influences. Social issues thus became literary themes especially ones that relate to major national challenges. This paper (Social Values in Selected Arabic Poems in Yorubaland, Nigeria) therefore focused on the poetic works of Yoruba Arabic poets on social issues.  The objectives of the study were to: (i) establish the availability of Arabic poetry on social issues in Yorubaland, (ii) analyse their contents in the light of socio-economic and political development of Nigeria. (iii) examine the artistic features of the social poetry, and (iv) evaluate selected poems with a view to appreciating their conformity with literary norms in Arabic. The study adopted both historical and analytical methods.